Determination of age and its correlation with biometric variables and seasonal reproductive indices of Leporinus obtusidens - Felizardo, Viviane de Oliveira; Andrade, Eliane Aparecida de; Melo, Carlos Cicinato Vieira; Murgas, Luis David Solis; Freitas, Rilke Tadeu Fonseca de; Andrade, Estefânia de Souza (Acta Scientiarum. Biological Sciences, 2015)
This study determined the age and its correlation with biometric variables and reproductive indices of piapara Leporinus obtusidens caught at the Funil Reservoir. We caught 133 specimens between September 2006 and August 2007. Weight, total length, standard length, depth, height, head length and radius of the scales were measured. The sex was determined by macroscopic examination of gonads. The age of each fish was determined by analyzing the growth rings on the scales. Seasonal differences in biometric variables were tested using the NK test at 5%. The correlation of age and radius of the scales with the biometric variables and reproductive indices were analyzed using the SAEG software. Fish individuals ranging from 3 to 14 years of age were caught. In the spring and summer, smaller fish were captured compared to those caught during the fall and winter. Females tended to have higher weight and morphometric values when compared to males. Age and radius of the scales were correlated with biometric variables in L. obtusidens. It can be concluded that the biometric variables of this species can be used as an indicator of age.